Si fertigation attenuates water stress in forages by modifying carbon stoichiometry, favouring physiological aspects - Rocha, Juan Ricardo [UNESP]; de Mello Prado, Renato [UNESP]; Teixeira, Gelza Carliane Marques [UNESP]; de Oliveira Filho, Antonio Santana Batista [UNESP] (Wiley, 2021)
Climate change has aggravated the occurrence of drought periods, affecting pasturelands in different regions of the world. Silicon attenuates water deficiency in several species, but there is a lack of research to verify whether Si can modify C stoichiometry and its effects in mitigating water deficit in forage plants. To this end, this research was carried out with the aim of evaluating whether Si supply via fertigation causes an increase in its absorption, stoichiometric modification of C and improvement in physiological variables and in the growth of Brachiaria cultivated under two soil water regimes (70% and 40% of water holding capacity in the soil). Two experiments were carried out with the cultivars BRS RB331 Ipyporã and Mavuno grown in pots filled with Quartzipsamments. In the experiments, the same treatments arranged in a 2 × 2 factorial scheme were applied, with Si application via fertigation applied to the soil and control (Si omission) combined with two soil water regimes (70% and 40% of the water retention capacity in the soil, adequate and deficient water contents, respectively). The two forages that received silicon via fertigation specially cultivated under water deficit had a greater accumulation of Si in the shoot, decreased C content and C:Si ratio and increased C use efficiency, and decreased rate of electrolyte leakage with increased relative water content, leaf water potential, chlorophyll b content, quantum efficiency of photosystem II and, consequently, increased growth and dry matter production. The present research shows that the use of Si via fertigation promotes a new strategy to mitigate water deficit in forages, based on the improvement of the physiological aspects of the plant resulting from the modification of carbon stoichiometry, thereby increasing C use efficiency.
Keywords: carbon use efficiency; drought stress; grasslands; plant nutrition